Principal's Program in Improving Teacher Performance During the Covid-19 Pandemic - Zakianti Zakianti; Yusrizal Yusrizal; Niswanto Niswanto (Tadbir : Jurnal Studi Manajemen Pendidikan, 2021)
This study aims to describe the principal's program in improving teacher performance during the Covid-19 pandemic at SD T. Nyak Arif Fatih Bilingual School, Banda Aceh. This type of research uses a qualitative approach. Data collection techniques through observation, interviews and documentation. The data analysis used in qualitative research is carried out interactively and takes place continuously until it is complete. Activities in data analysis, namely data reduction, presentation, drawing conclusions and verification. The results of the study concluded that: First, improving teacher performance during the Covid-19 pandemic by implementing a learning application training program to support the online learning process. This training is carried out regularly until the teachers are proficient in running the application. Second, the application of Lesson Study. Lesson Study is an assessment activity carried out by teachers/lecturers together and continuously to test and improve the effectiveness of learning and form a learning community. With Lesson Study, it is hoped that teachers will be more active and share knowledge with each other to support the learning process during the COVID-19 pandemic. Third, the application of the hybrid learning method program. Hybrid Learning is a learning method in which there is a combination of face-to-face learning in the classroom and coupled with offline and online learning using computers. The application of the hybrid learning method in the Covid-19 pandemic era is very helpful for students who are self-isolation, to be able to feel learning like in a classroom but in a different place by being integrated by technology. Through programs run by school principals during the pandemic in improving teacher performance so that it can run as expected and be able to give birth to quality next generation. To be able to feel learning like in a classroom but in a different place by being integrated by technology. Through programs run by school principals during the pandemic in improving teacher performance so that it can run as expected and be able to give birth to quality next generation. To be able to feel learning like in a classroom but in a different place by being integrated by technology. Through programs run by school principals during the pandemic in improving teacher performance so that it can run as expected and be able to give birth to quality next generation.